CORRELATION BETWEEN BLOOD PRESSURE AT ADMITTED EMERGENCY ROOM AND CLINICALLY OUTCOME IN ACUTE THROMBOTIC STROKE PATIENTS - Rianawati, Sri Budhi; Aurora, Habiba; Nugrahanitya, Yulia (Malang Neurology Journal, 2015)
Background. High blood pressure is the first risk factor in stroke, but it is possible that low blood pressure causes stroke, although it is a few incident. Objective. To know the relation between blood pressure on arrival time in stroke unit and the clinical outcome of acute thrombolytic stroke patients using NIHSS score. Methods. Using cohort retrospective study, 38 samples were selected by consecutive method. The variable measured in this research is systolic blood pressure (SBP), diastolic blood pressure (DBP), and Mean Arterial Pressure (MAP) at the first time in stroke unit to NIHSS patients in the last day nursing (10-14 days). Results. Based from Spearman correlation test, SBP (p = 0,136; r = 0,246), DBP (p = 0,586; r = 0,091), and MAP (p = 0,171; r = 0,227) indicate that have not significant correlation with NIHSS and indicate that very weak correlation. Conclusion. Systolic blood pressure (SBP), diastolic blood pressure (DBP), and Mean Arterial Pressure (MAP) have not significant correlation with NIHSS and indicate that very weak correlation. Study is needed to understand the relation without any treatment influence and confounding factor.